Current Controller Based Power Management Strategy for Interfacing DG Units to Micro Grid - N. Chaitanya; P. Sujatha; K. Chandra Sekhar (Institute of Advanced Engineering and Science, 2017)
This paper proposes a power management strategy of parallel inveters based system, to enhance the power generation capacity of the existing system with distributed energy sources one has to choose DG source based inverter connected in parallel with the existing system.Two DG sources PV, Fuel cells feeds the DC voltage to two parallel inverters connected to the grid. Fixed band hysteresis current control with Instantaneous p-q power theory is adopted to create an artificial environment. Two parallel inverters are able to deliver the harvested power from PV, FC to grid and able to balance the load Without communication between parallel inverters this controller having the capability of load following, the harmonic components of currents at output of inverter are also very low; this will automatically reduces the circulating currents between parallel inverters. Simulation studies are carried out to investigate the results of PV, FC systems connected to the utility grid.